PHArmed: A Biological Process for PHA Production from Apple Waste Residues - Maria Teresa Oliveira; José Francisco Marques; Markus Driller; Rita Sousa Branco; Sofia Pinto; Rita Barros (U.Porto Journal of Engineering)
PHArmed is an innovative Portuguese company responsible for producing PHA in its rawest form, using renewable carbon sources from apple residues. With the increasing environmental urge to find alternatives to regular plastic and an existing expensive way of producing PHA, PHArmed solves both issues with a biodegradable and cheaper product, with biocompatible properties that make it viable for both medical and pharmaceutical industries. Using apple waste from other companies reduces production costs and helps solve the issue regarding waste treatment. After a complete definition of the manufacturing process, the industrial plant would be installed in Pombal, near two large apple waste-producing companies, with a work team of 15 operators. An economic assessment was performed, and an initial 11.8 M€ investment was estimated for the first year. The project was shown to be economically viable and capable of generating a financial surplus, reaching a break-even point after six years.